ECONOMIC EFFICIENCY OF JERUSALEM ARTICHOKE CULTIVATION (HELIANTHUS TUBEROSUS L.) IN THE CHUI VALLEY OF KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article presents the average data of three-year production tests of Jerusalemartichoke varieties previously zoned by us for economic efficiency in the Chui Valley of Kyrgyzstan. The Blank variety has the highest profit (1341900 soms per 1 ha), with a profitability level of552.9%, followed by the Leningrad variety with a profitability of 381.9%. The French purple variety has relatively low values – 307.1%. The other three varieties – Salad, Nakhodka and Interesthave approximately the same profitability levels: 344.3-248.4%. It turned out that the cultivationof Jerusalem artichoke as a raw material for the food, pharmaceutical industry and as feed for farmanimals and birds is economically more profitable compared to other agricultural plants.
Keywords: jerusalem artichoke, economic efficiency, productivity, technological map, net profit, profitability level.